Provoked by Art: A Retrospective - Cole, Ardra L. (Art/Research International, 2025)
In 1996, while at a conference in New York City, I happened upon an art exhibit that changed the trajectory of my academic career. In this article, I recount part of my experience of engaging with the installation art of Edward and Nancy Reddin Kienholz and its transformative impact on my scholarly work. I reflect on some of the ways in which that chance moment unleashed my latent frustrations about the hegemonic conventions of academic research and inspired a path of possibilities for how social science research could be more meaningful in the lives of individuals and communities. I conclude with a note on the importance of open-mindedness, imagination, and a respect for serendipity in inspiring creativity, informing and, possibly, transforming research.